Frugal innovations for healthcare: a toolkit for innovators - Prime,M; Bhatti,Y; Harris,M; Darzi,A (Academy of Management, 2017)
Global health systems face significant challenges over the coming years to meet the increasing demands of ageing populations, the growing burden of chronic disease and the exponential cost of healthcare delivery. In response innovators from around the world are beginning to develop solutions that focus on reducing the cost of care; widen access to care; and challenge the dogma that more is better. So-called frugal innovations are defined as “means or ends, to do more with less, for the many” (Bhatti, 2014). This paper seeks to ask, “How can we identify frugal innovations for healthcare and how are they achieving frugality?” with the specific objective of developing a frugal innovation toolkit for healthcare. An emergent, embedded, mixed-methods research strategy was employed. A pilot study was used to develop the Frugal Innovation for Healthcare - Identification Tool (FIH-ID tool). A larger study was undertaken to identify a cohort of frugal innovations, evaluate the application of the FIH-ID tool, and assess the processes and strategies employed by frugal innovators. 56 semi-structured interviews were undertaken with 90 representatives of 28 healthcare innovations exhibiting at the World Innovation Summit for Health (WISH) 2015. 15 frugal innovations for healthcare were identified. Inter-observer agreement for application of the FIH-ID tool demonstrated a high proportion of agreement (Po = 0.714), and a “fair” Cohen’s Kappa score (K = 0.499). A thematic analysis identified key strategies applied by individuals or organizations to produce frugal innovations. These include: the application of new information & communication technologies; harnessing existing networks; simplification; changing the location of care; and task-shifting. This paper presents a toolkit of strategies for identifying and creating frugal innovations for healthcare. This research suggests that the FIH-ID tool is a reliable means of identifying exampl